The Autophagoproteasome a Novel Cell Clearing Organelle in Baseline and Stimulated Conditions - Lenzi, Paola; Lazzeri, Gloria; Biagioni, Francesca; Busceti, Carla L.; Gambardella, Stefano; Salvetti, Alessandra; Fornai, Francesco (Frontiers in Neuroanatomy, 2016)
Protein clearing pathways named autophagy (ATG) and ubiquitin proteasome (UP) control homeostasis within eukaryotic cells, while their dysfunction produces neurodegeneration. These pathways are viewed as distinct biochemical cascades occurring within specific cytosolic compartments owing pathway-specific enzymatic activity. Recent data strongly challenged the concept of two morphologically distinct and functionally segregated compartments. In fact, preliminary evidence suggests the convergence of these pathways to form a novel organelle named autophagoproteasome. This is characterized in the present study by using a cell line where, mTOR activity is upregulated and autophagy is suppressed. This was reversed dose-dependently by administering the mTOR inhibitor rapamycin. Thus, we could study autophagoproteasomes when autophagy was either suppressed or stimulated. The occurrence of autophagoproteasome was shown also in non-human cell lines. Ultrastructural morphometry, based on the stochiometric binding of immunogold particles allowed the quantitative evaluation of ATG and UP component within autophagoproteasomes. The number of autophagoproteasomes increases following mTOR inhibition. Similarly, mTOR inhibition produces overexpression of both LC3 and P20S particles. This is confirmed by the fact that the ratio of free vs autophagosome-bound LC3 is similar to that measured for P20S, both in baseline conditions and following mTOR inhibition. Remarkably, within autophagoproteasomes there is a slight prevalence of ATG compared with UP components for low rapamycin doses, whereas for higher rapamycin doses UP increases more than ATG. While LC3 is widely present within cytosol, UP is strongly polarized within autophagoproteasomes. These fine details were evident at electron microscopy but could not be deciphered by using confocal microscopy. Despite its morphological novelty autophagoproteasomes appear the natural site where clearing pathways (once believed to be anatomically segregated) co-exist and they are likely to interact at molecular level. In fact, LC3 and P20S co-immunoprecipitate, suggesting a specific binding and functional interplay, which may be altered by inhibiting mTOR. In summary, ATG and UP often represent two facets of a single organelle, in which unexpected amount of enzymatic activity should be available. Thus, autophagoproteasome may represent a sophisticated ultimate clearing apparatus.